Influence of soil variables at the L Band: backscattering coefficient simulations for sunflower in early stages - Mieza, M. Soledad (2021)
SAR backscattering coefficient (σ⁰) of crops depends on the operational frequency, polarization and incidence angle of the acquisition system, the dielectric behaviour of crops, and soil-related variables such as the volumetric moisture (mv) and its roughness. In SAR applications, surface roughness is usually characterized by two parameters: the standard deviation of the surface height to a reference height or rms height (s) and the autocorrelation length. The autocorrelation length, defined as the distance at which the correlation function drops to 1/e, describes the surface periodicity and indicates to what extent two separate points can be considered correlated. For crops in their early stages, soil characteristics play a crucial role in σ⁰ due to the low vegetation development. In this work, we present σ⁰ simulations for sunflower (early stages) using a model proposed by for the L Band; specifically, the frequency was set to that of the SAOCOM instruments (1.275 GHz).